The perception of the practitioners and students towards the subject of forensic accounting and fraud examination - Septarina Prita Dania Sofianti; Unti Ludigdo; Gugus Irianto (Journal of Economics, Business, and Accountancy Ventura, 2014)
This research aims to analyze the insight of practitioners, academicians, and accounting students toward forensic accounting and fraud examination course as if integrating into accounting curriculum. It also analyzes the difference of practitioners, academicians and accounting students insight’s regarding demand, interest, career, obstacles, benefits and topics of forensic accounting and fraud examination as if integrating into accounting curriculum. The results indicate that practitioners, academicians and accounting students are encouraging forensic accounting and fraud examination course should be integrated into accounting curriculum. It also indicate that there were some significant differences exist regarding demand, interest, career, obstacles, beneficial and topics of forensic accounting and fraud examination (FAFE). The results are useful for universities that consider integrating forensic accounting and fraud examination course into accounting curriculum, hence redesign their forensic accounting and fraud examination course that relevant with Indonesian’s necessitate.